LEGAL REVIEW OF INDUSTRIAL RELATIONS DISPUTES IN THE CASE OF ALLEGED UNION BUSTING AT PT DAECHANG AUTOMOTIVE INDONESIA IN 2026 - Reza Septian Pradana (PT. Radja Intercontinental Publishing, 2026)
Industrial relations disputes triggered by alleged union busting practices demonstrate the increasing complexity of conflicts between workers and employers, particularly in the context of freedom of association. In practice, actions that lead to weakening labor unions are often disguised in seemingly legal managerial policies, such as termination of employment (PHK). This study aims to analyze the types and characteristics of industrial relations disputes, examine alleged union busting practices based on applicable legal provisions, and determine the appropriate dispute resolution mechanism in the case of PT Daechang Automotive Indonesia in 2026. This study uses a qualitative approach with a normative juridical method and a case study design, with secondary data obtained through literature studies covering primary legal materials, secondary legal materials, and empirical sources in the form of news articles. The results show that the disputes that occur are multidimensional, including disputes over termination of employment and disputes regarding rights related to freedom of association. The characteristics of the disputes are marked by unequal bargaining positions between workers and employers, policy selectivity towards union officials, and the development of the conflict from individual to collective. Legally, there are strong indications of union busting practices, demonstrated by the fulfillment of elements of violations, including actions that hinder union activities and the use of efficiency reasons that are not in line with empirical conditions. The most appropriate resolution mechanism is through mediation as the primary effort, supported by the possibility of litigation through the Industrial Relations Court to ensure legal certainty and the protection of workers' rights. This research provides a theoretical contribution to the development of industrial relations studies as well as a practical contribution to strengthening protection of freedom of association and workers' welfare.